2017
DOI: 10.1002/ldr.2675
|View full text |Cite
|
Sign up to set email alerts
|

A State‐Space Analysis of Soil Organic Carbon in China's Loess Plateau

Abstract: An accurate estimation of soil organic carbon (SOC) is important for the evaluation and management of carbon (C) flux in terrestrial ecosystems. However, there is little work on the spatial variability of SOC in deep soils and its driving factors. Thus, the objective of the study was to derive the primary factors dominating the spatial distribution of SOC in different soil layers with the use of the autoregressive state‐space approach. The concentration of SOC was measured to the depth of 500 cm (n = 86) along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 61 publications
(120 reference statements)
3
22
0
Order By: Relevance
“…High MAP and MAT also resulted in a high litter decomposition rate on the land surface and a large release of organic carbon (Han et al, ; W. Zhao et al, ), which accelerated the accumulation of organic carbon in the soil. In addition to climate, high clay content usually leads to the association of organic carbon compounds with fine soil particles (Bazzoffi, Mbagwu, & Chukwu, ; Bronick & Lal, ; Jia, Yang, et al, ), which provided chemical protection for SOC against microbial decomposition (Razafimbelo et al, ). Moreover, high SOM and clay content stimulated aggregation of soil particles (Bazzoffi et al, ), which in turn provided physical protection for SOC from decomposition (Bronick & Lal, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High MAP and MAT also resulted in a high litter decomposition rate on the land surface and a large release of organic carbon (Han et al, ; W. Zhao et al, ), which accelerated the accumulation of organic carbon in the soil. In addition to climate, high clay content usually leads to the association of organic carbon compounds with fine soil particles (Bazzoffi, Mbagwu, & Chukwu, ; Bronick & Lal, ; Jia, Yang, et al, ), which provided chemical protection for SOC against microbial decomposition (Razafimbelo et al, ). Moreover, high SOM and clay content stimulated aggregation of soil particles (Bazzoffi et al, ), which in turn provided physical protection for SOC from decomposition (Bronick & Lal, ).…”
Section: Discussionmentioning
confidence: 99%
“…The restoration and reconstruction of degraded ecosystems are essential for the development of degraded lands and for increasing the functionality of the ecosystem in the Loess Plateau (Jia, Shao, et al, ; Jia, Shao, Yu, Zhang, & Binley, ). Afforestation on abandoned farmlands is one of the most effective ways to prevent soil erosion, to remedy degraded lands, and to sequester C, and this approach is used widely around the world (Deng, Dong, Cai, & Ding, ; García‐Díaz et al, ; Jia, Shao, et al, ; Jia, Yang, Zhang, Shao, & Huang, ; John, Chen, Lu, & Wilske, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fine particles and high capillary porosity would improve the water‐holding capacity of the soil. Soil organic carbon can also increase the capacity of the soil to store and retain water by improving soil structure (Jia, Yang, Zhang, Shao, & Huang, ). The elevation varied little within the plot, and the vegetation was sparse and slightly degraded, which would contribute little to the distribution of SWC on the scale of this study (Wang, Zhang, Chen, et al, ; Zhang, Zhang, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to Xu et al (2014), who found that land‐use types and reclamation time significantly influenced soil salinity in coastal areas. Jia et al (2017) also reported that land‐use patterns could significantly affect solute transports and water balances in soil systems. Vegetation coverage and clay content were significantly and negatively correlated to SSC in the two transects, which was consistent with previous findings that greater vegetation coverage corresponded to lower SSC (Mackinnon et al, 2001; Fernández‐Buces et al,2006).…”
Section: Discussionmentioning
confidence: 98%